Participant and caregiver perspectives on health feedback from a healthy lifestyle check - Miranda D. Lee; Cervantée E. K. Wild; Ken J. Taiapa; Ngauru T. Rawiri; Victoria Egli; Sarah E. Maessen; Yvonne C. Anderson (Wiley, 2024)
Abstract Introduction The usual output following health consultations from paediatric services is a clinical letter to the referring professional or primary care provider, with a copy sent to the patient's caregiver. There is little research on how patients and caregivers perceive the letter content. We aimed to: first understand child, young people and caregiver experiences of and preferences for receiving a health feedback letter about the child/young person's health measures within a healthy lifestyle programme; and second to provide a set of recommendations for designing letters to children, young people and their families within a healthy lifestyle programme. Methods This qualitative study, informed by Kaupapa Māori principles, included focus groups of children aged 5-11 years and young people aged 12-18 years who were participants in a healthy lifestyle programme in Taranaki, Aotearoa New Zealand and of their respective caregivers (total n = 47). Discussions were audio‐recorded, transcribed and analysed using thematic analysis. Findings Key themes were identified: letters sometimes acted as 'discourses of disempowerment'-some participants experienced a lack of safety, depersonalisation with medical jargon and 'feeling like a number'. Participants described the need for acknowledgement and affirmation in written communication-health feedback should include validation, choice regarding content, respectful tone and a strengths‐based approach to health messages. Interpretation Letters to referrers, copied to families, can be perceived as disempowering, and participant and caregiver perspectives of content should be considered. This study challenges conventional practice in communicating health feedback with broader implications for written communication in healthcare. We propose separate letters aimed at the child/young person and their caregiver that offer choice in the information they receive. The administrative burden of multiple letters can be mitigated by advances in digital health. Patient Contribution This study originated in response to feedback from service users that current health feedback was not meeting their needs or expectations. Patient perspectives, especially from children, are rarely considered in the generation of clinic letters from health professionals. Participants were child participants in the community‐based clinical service and their caregivers, and care was taken to represent the demographic backgrounds of service users. Collection and interpretation of Māori data were led by researchers who were local community members to ensure prioritisation and preservation of participant voice. Where possible, results are illustrated in the text by direct quotes from participants, whose identities are protected with a pseudonym.